Pharmacological In vivo test to evaluate the antidepressant activity of polyherbal formulation - Kumari, Rinki; Ilango, K.; Singh, G.P.I.; Dubey, G.P. (Nepal Journal of Biotechnology, 2019)
The antidepressant effects of the polyherbal formulation (PF) (contain four extracts of medicinal plants namely: Nyctanthes arbortristis, Hippophae salcifolia, Ocimum tenuiflorum and Withania somnifera ) was examined by evaluating the extent of reduction of behavioural alterations and neurotransmitter in the rats stressed by forced swim test (FST). In the present study, compared with the model control group (FST), the altered behavioural parameters were attenuated significantly (P < 0.05) in the group treated with the PF (100, 200 and 400 mg•kg−1), comparable with the standard drug treated group, Sertraline (10mg•kg−1). The PF and Sertraline significantly (P < 0.05) increased the level of the neurotransmitter such as serotonin, dopamine, acetylcholine and noradrenalin whereas decreased the level of monoamine oxidase along with oxidant in the brain of the stressed rats. PF and Sertraline were also involved in the reduced oxidant and generated antioxidant in the stressed rats. The results indicated that polyherbal formulation exhibited significant antidepressant activity, as indicated by its ability to decrease force swim stress, induced immobility time in rats as well as restoring the biogenic amines to normal level that were altered by the swim induced stress in whole rat brain. Therefore, PF can be a potential candidate for treatment of depression as well as a potent antidepressant. However, further studies are required to substantiate the same.